Application of Business Ethics By Shirkah Contract: A Case Study of Indonesian Farmer Tradition - Any Setianingrum; Muslikh; Lily Deviastri (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
Economists argue that positivism refers to science and economic activities should be value-free. This means that the norm variable is not included as a variable that has an important meaning for both output and production input. This is not the case with Islamic economics, which firmly states that economic activity is bound to value or is not value-free. This research aims to show evidence of shirkah or profit-sharing contracts and to dissect how elements of values and ethics accompany the business activities of Indonesian farming communities. The method used is a qualitative approach with case study techniques. Literature studies are also used to strengthen the validation and triangulation stages. This research shows that Shirkah contracts are found in agricultural activities in various regions in Indonesia, including those known as maro (50:50), mertelu (1:3), etc. Shirkah, as one of the contracts in Sharia finance, is an actual implementation of enforcing norms and ethics. The Shirkah contract manages the risks inherent in all business cycles, both during profits and losses, which is typical in all sectors. Shirkah contracts systematically work and control competition and business risks with an ethical and normative approach. The Shirkah contract also suppresses economic injustice and unequal distribution of resources and business profits. The domino effect of the values of the sharia contract is not only limited to production-sharing agreements between sharecroppers and land owners but also spreads to the spirit values of sale and purchase (Murabaha) and rental (ijarah) agreements and includes broad implications for all aspects life. Farmers and cultivators are actively involved in upholding the values of justice, risk sharing, and togetherness in facing the cycle of profit and loss that automatically occurs as a lifestyle. Musharaka, Morals-ethics, Risk management, Way of life